Pengembangan Program Studi Manajemen Zakat dan Wakaf Fakultas Syariah IAIN Surakarta Berbasis Kebutuhan Masyarakat - Hayatuddin, Ah. Kholis (UIN Sunan Kudus, 2019)
The Importance of Existence from Mazawa Study Program must also be balanced with the development of study programs that meet the needs of the community, namely to produce the energy needed by the community. Therefore the development of Mazawa's products that are attractive to people's needs is very important, with the hope that quality can compete at regional, national and even international levels. The development of advanced communities with complex problems is a challenge for the development of Zakat Management and Waqf needed to predict future community needs.